Mulibrey nanism: Two novel mutations in a child identified by Array CGH and DNA sequencing. Issue 8 (3rd June 2016) - Mozzillo, Enza; Cozzolino, Carla; Genesio, Rita; Melis, Daniela; Frisso, Giulia; Orrico, Ada; Lombardo, Barbara; Fattorusso, Valentina; Discepolo, Valentina; Della Casa, Roberto; Simonelli, Francesca; Nitsch, Lucio; et al.
Abstract : In childhood, several rare genetic diseases have overlapping symptoms and signs, including those regarding growth alterations, thus the differential diagnosis is sometimes difficult. The proband, aged 3 years, was suspected to have Silver–Russel syndrome because of intrauterine growth retardation, postnatal growth retardation, typical facial dysmorphic features, macrocephaly, body asymmetry, and bilateral fifth finger clinodactyly. Other features were left atrial and ventricular enlargement and patent foramen ovale. Total X‐ray skeleton showed hypoplasia of the twelfth rib bilaterally and of the coccyx, slender long bones with thick cortex, and narrow medullary channels. The genetic investigation did not confirm Silver–Russel syndrome. At the age of 5 the patient developed an additional sign: hepatomegaly. Array CGH revealed a 147 kb deletion (involving TRIM 37 and SKA2 genes) on one allele of chromosome 17, inherited from his mother. These results suggested Mulibrey nanism. The clinical features were found to fit this hypothesis. Sequencing of the TRIM 37 gene showed a single base change at a splicing locus, inherited from his father that provoked a truncated protein. The combined use of Array CGH and DNA sequencing confirmed diagnosis of Mulibrey nanism. The large deletion involving the SKA2 gene, along with the increased frequency of malignant tumours in mulibrey patients, suggests closed monitoring for cancer of our patient and his mother. Array CGH should be performed as first tier test in all infants with multiple anomalies. The clinician should reconsider the clinical features when the genetics suggests this. © 2016 Wiley Periodicals, Inc.